The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.schres.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Medial temporal lobe structure and cognition in individuals with schizophrenia and in their non-psychotic siblings

Abstract: Medial temporal lobe (MTL) structures play a central role in episodic memory. Prior studies suggest that individuals with schizophrenia have deficits in episodic memory as well as structural abnormalities of the medial temporal lobe (MTL). While correlations have been reported between MTL volume loss and episodic memory deficits in such individuals, it is not clear whether such correlations reflect the influence of the disease state or of underlying genetic influences that might contribute to risk. We used hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 71 publications
3
41
0
Order By: Relevance
“…Thus, the hippocampus proper is abnormal in young individuals at FHR, consistent with results observed in older relatives. The parahippocampal gyrus (PHG) has been studied less frequently and the only published study of PHG in young relatives has shown thinner cortex in nonpsychotic relatives than in controls (Karnik-Henry et al, 2012). We had found smaller PHG volume in older relatives .…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Thus, the hippocampus proper is abnormal in young individuals at FHR, consistent with results observed in older relatives. The parahippocampal gyrus (PHG) has been studied less frequently and the only published study of PHG in young relatives has shown thinner cortex in nonpsychotic relatives than in controls (Karnik-Henry et al, 2012). We had found smaller PHG volume in older relatives .…”
Section: Introductionmentioning
confidence: 66%
“…We had found morphometric abnormalities in PHG in a prior larger study of adult relatives using these methods . To date, two studies of young relatives have shown excessive cortical thinning in FHR (Byun et al, 2012;Karnik-Henry et al, 2012) but there were no significant differences in parahippocampus in the one study that measured volumes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, neuroimaging evidence has suggested aberrations in this region in previous studies of schizophrenia patients and their first-degree relatives, particularly left-lateralized deficits (Friston et al, 1992;Karnik-Henry et al, 2012;Meisenzahl et al, 2008). Hoptman et al (2010) also found increased ALFF in the left hippocampus and parahippocampal gyrus in subjects with schizophrenia.…”
Section: Discussionmentioning
confidence: 86%
“…On a backdrop of a generalized cognitive impairment, deficits in declarative memory appear particularly severe among persons with chronic and first-episode schizophrenia spectrum disorders (SSD; Aleman, Hijman, de Haan & Kahn, 1999;Heinrichs & Zakzanis, 1998;Karnik-Henry et al, 2012;Mesholam-Gately, Giuliano, Goff, Faraone, & Seidman, 2009;Weiss & Heckers, 2001). Moreover, memory performance is one of the strongest predictors of functional outcome, as compared to a host of other cognitive measures, clinical symptoms, and demographic variables (Ranganath, Minzinberg, & Ragland, 2008).…”
mentioning
confidence: 99%